Cross-linking of a Commercial Starch using Epichlorohydrin and Sodium Trimetasphosphate - Sabatier C., Juan (2005)
Crosslinking of a commercial starch with epichlorohydrin and sodium trimetaphosphate was studied. These reactions were monitored by viscosity measurements, while products were characterized by spectroscopic methods, electron microscopy and determining the swelling on several fluids. Epichlorohydrin dose has a significant influence on the results of crosslinking, meanwhile sodium hydroxide catalyzes the reaction with sodium trimetaphosphate and this crosslinking reagent produces higher-swelling hydrogels.